OPTIONS - BENDA,G; S,P (Tufts Archival Research Center, 2007)
Marginalia; Handwritten; Illegible/Difficult to Read; Presentation on indoor air quality. Discusses Philip Morris' Accommodation program which attempts to accommodate both smokers and non smokers without the use of a ban.